2009
DOI: 10.1161/circep.108.786665
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Atrial Fibrillation

Abstract: Background-Heritability may play a role in nonfamilial atrial fibrillation (AF). We hypothesized that a monozygotic (MZ) twin whose co-twin was diagnosed with AF would have an increased risk of the disease compared with a dizygotic (DZ) twin in the same situation. Methods and Results-A sample of 1137 same-sex twin pairs (356 MZ and 781 DZ pairs) in which one or both members were diagnosed with AF were identified in The Danish Twin Registry. Concordance rates were twice as high for MZ pairs than for DZ pairs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
119
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(127 citation statements)
references
References 33 publications
(35 reference statements)
5
119
0
3
Order By: Relevance
“…6 A number of studies have demonstrated that AF and in particular lone AF have a substantial genetic component. [7][8][9][10][11][12][13] Oyen et al 14 have recently shown that an individual's risk of developing lone AF at a young age, increases drastically with both increasing number of relatives with lone AF and decreasing age at onset of the disease in these relatives, indicating an underlying genetic component in early onset lone AF.…”
Section: Introductionmentioning
confidence: 99%
“…6 A number of studies have demonstrated that AF and in particular lone AF have a substantial genetic component. [7][8][9][10][11][12][13] Oyen et al 14 have recently shown that an individual's risk of developing lone AF at a young age, increases drastically with both increasing number of relatives with lone AF and decreasing age at onset of the disease in these relatives, indicating an underlying genetic component in early onset lone AF.…”
Section: Introductionmentioning
confidence: 99%
“…; up to 15% of these cases have a positive family history, and are thus defined as familial AF (9). Increasing evidence demonstrates the familial aggregation of AF and an enhanced vulnerability to AF in the close relatives of patients with AF, suggesting that genetic defects may be involved in the pathogenesis of AF in a subset of patients (10)(11)(12)(13)(14)(15)(16). Genome-wide genetic linkage analysis with highly polymorphic microsatellite markers mapped susceptibility loci for AF on human chromosomes 10q22, 6q14-16, 11p15.5, 5p13, 10p11-q21 and 5p15, of which AF-causing mutations in two genes, KCNQ1 on chromosome 11p15.5 and NUP155 on chromosome 5p13, were identified and functionally characterized (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…However, in 30-45% of AF patients, no established risk factors are identified by routine procedures, and such AF is defined as 'idiopathic' or 'lone' (1), of which at least 15% have a positive family history, so termed familial AF (7). Growing evidence has documented the familial aggregation of AF and an enhanced susceptibility to AF in the close relatives of patients with AF, indicating that hereditary defects may play an important role in the pathogenesis of AF in a subset of patients (8)(9)(10)(11)(12)(13)(14). Genome-wide linkage analysis with polymorphic genetic markers mapped multiple susceptibility loci for AF on human chromosomes 10q22, 6q14-16, 11p15.5, 5p13, 10p11-q21 and 5p15, of which AF-causing mutations in 2 genes, KCNQ1 on chromosome 11p15.5 and NUP155 on chromosome 5p13, were identified and functionally characterized (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%